STRATEGI PENGEMBANGAN AYAM BIROMARU DALAM UPAYA PENYEDIAAN BIBIT AYAM PEDAGING LOKAL - Awaluddin Awaluddin (Indonesian Journal of Applied Sciences, 2012)
This study was aimed to know the heritability of body weight of age 1 to 12 weeks, the most appropriate selection methods, the correlation coefficient of estimate breeding value, the best selection standards, the percentage of chicken carcasses and toformulate development strategy as a locally provision chicken broiler. This study used six males and 18 females. While technically a marriage using the natural way. The research data obtained from 121 of the tail, which consisted of 37 males and 84 females. Data were analyzed by using the VCE 6 (Groneveld, 2008), PEST (Groneveld, 1999), and SAS 9 using univariate Animal Models. The results of this study have (1) The heritability of body weight from week 1 to week 12 ranged from 0.448 ± 0.076 to 0.500 ± 0.489, (2) To improve the genetic quality of Biromaru chicken should be done by the method of mass selection or individual selection on the weight agencies and other properties of highly correlated with body weight, (3) The correlation coefficient of body weight breeding value  of 1 to 12 weeks of age in chickens ranged from 0.2019 between the age of 10 weeks to the age of one week, until 0.9217 at coefficient correlation between the age ?10 weeks of age to the age of 9 weeks, (4) The standard of selection is best depends on the selection standards that we use, if we use the standard selection of 8 weeks of selection should be done at the age of 4 weeks with a correlation coefficient of breeding value of 0.7138, whereas if we use the standard 12 weeks of selection then the selection should be done at age 8 with a correlation coefficient breeding weeks value of 0.6264, (5) The percentage of chicken carcasses Biromaru at the age of 4, 8 and 12 weeks in a sequence that is 56 , 10%, 60.31% and 61.64%, and(6) Poultry Supply Biromaru Chicken (DOC) Model with closed nucleus breeding scheme with two levels namely; nucleus andbranchs.